“You’re not taught to think about the words you use and then it just perpetuates”— a qualitative examination of medical students’ perspectives of stigmatising language in healthcare - Saakshi Daswani; Elizabeth Gorecki; Lisa Mellon (BMC Medical Education)
Abstract Background Stigmatising language is used commonly in healthcare, affecting healthcare providers’ perceptions of patients and care delivery. Using person-first language is best practice, however, it does not reflect reality. Method This study examined medical students’ perspectives on stigmatising language in healthcare. Twenty-one medical students at the RCSI University of Medicine and Health Sciences participated in four focus group interviews; a thematic analysis of the data was conducted. Results Seven themes were identified: prevalence of stigmatising language, its impact on students and patients, being sensitive versus medically accurate, evolving nature of recommendations for language use, barriers to changing practice, power dynamics and cultural context influencing language use, stigmatising language being a societal issue. Participants provided recommendations for improving language use in healthcare: open discussions and student feedback on language in the learning environment, lecturers signposting person-first language, training workshops on person-first language for clinicians and lecturers, and social intelligence skills training. Conclusion Study findings highlight the impact of stigmatising language in healthcare. To address this issue and inform guidance for future generations of professionals, medical students recommended more open dialogue and improved social intelligence.